Manpower Studies Occupational Pattern in Manufacturing Industries India 1956 - Planning Commission (Planning Commission, 1956)
This study represents the results of a Sample Survey of Occupational Pattern in Manufacturing Industries in 1956, carried out through the field agency of the Sample Survey of Manufacturing Industries (SSMI) by Planning Commission (Perspective Planning Division) working in collaboration with the Indian Statistical Institute.
Scientific and Technical Manpower and Perspective Planning Division
Government of India Planning Commission